Optical time-lapsed in situ mechanochemical studies on metal halide perovskite systems - Yonghao Xiao; David G. Bradley; Wei Xin Chan; Xinwen Hu; Lian Xiao; Zhenpeng Liu; Zi Yang Tan; Xin Zhao; Chenfei Li; Mansour Sadek; Vikash Kumar Ravi; Ying Hern Tam; et al. (Nature Communications)
Abstract Metal halide perovskites are attractive for optoelectronic applications, but the existing solution-based synthetic methods rely on hazardous solvents and lack reproducibility. To overcome these challenges, solvent-free mechanochemical synthesis of perovskites can be conducted, although traditional opaque ball milling equipment hinder real-time monitoring of the reaction progress. Herein, mechanochemistry was performed with time-lapsed in situ (TLIS) measurements to elucidate the optical properties during the synthesis. The TLIS spectrometer enabled real-time observation of the impact of varying the compositions on the absorption properties of formamidinium/methylammonium lead iodide (FA x MA1-x PbI3, x = 0 to 1) and facilitated optimization of the synthesis duration. Moreover, we can accelerate the evaluation and directly observe the effects of different synthetic strategies for enhancing the photoluminescence quantum yield and stability of the perovskites, providing near-infrared (NIR) emitting tin-based perovskites FASnI z Br3-z (where z = 0 to 3) with core-shell structures. Intriguingly, halide ion migration was deduced in lead-free double perovskites Cs2Na y Ag1-y BiCl6 (y = 0 to 1.0) at room temperature during aging after mechanochemical activation. Our work provides insights into the mechanochemistry of compounds with low thermodynamic barriers.